ESP, metacognition, and financial reporting practice: The moderating role of learning motivation - Yosef Paseli Dheghu; Marianus Hendrilensio Sanga; Resvina Situmorang; Olivia Latumahina; Alini Wora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study examines the influence of English for Specific Purposes (ESP) learning and metacognitive learning strategies on accounting students' financial reporting practices, thereby strengthening language-based professional competencies in vocational higher education. The population consisted of 612 third- and fifth-semester accounting students at Politeknik Negeri Kupang, and 239 were selected using proportional stratified random sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that ESP learning does not significantly affect students' financial reporting practice (β = 0.121, t = 1.763), indicating that linguistic improvement alone does not translate into better technical reporting performance. Conversely, metacognitive learning strategies have a strong positive effect (β = 0.367, t = 4.580), indicating that students who plan, monitor, and evaluate their learning are more able to apply accounting concepts accurately. Learning motivation does not moderate the effect of ESP learning (β = 0.020, t = 0.196) nor the effect of metacognitive strategies (β = –0.037, t = 0.477), suggesting that motivation does not alter these relationships. The model explains 41.6% of the variance in students' financial reporting practice, underscoring the dominance of cognitive and self-regulatory processes in shaping competence. The study recommends integrating ESP instruction with strategy-based and practice-oriented learning approaches and suggests future research employing longitudinal or experimental designs.